Silk Fibroin Particles as Carriers in the Development of Hemoglobin‐Based Oxygen Carriers - Marisa O. Pacheco; Henry M. Lutz; Jostin Armada; Nickolas Davies; Isabelle K. Gerzenshtein; Alaura S. Cakley; Bruce D. Spiess; Whitney L. Stoppel (Advanced NanoBiomed Research, 2023)
Oxygen therapeutics has a range of applications in transfusion medicine and disease treatment. Synthetic molecules and all‐natural or semisynthetic hemoglobin‐based oxygen carriers (HBOCs) have seen success as potential circulating oxygen carriers. However, many early HBOC products stalled in development due to side effects from excess hemoglobin in the blood stream and hemoglobin entering the tissue. To overcome these issues, research has focused on increasing the molecular diameter of hemoglobin by polymerizing hemoglobin molecules or encapsulating hemoglobin in liposomal carriers. This work leverages the properties of silk fibroin, a cytocompatible and nonthrombogenic biopolymer, known to entrap protein‐based cargo, to engineer a fully protein‐based oxygen carrier. Herein, an all‐aqueous solvent evaporation technique is used to form silk particles via phase separation from a bulk polyvinyl alcohol phase. Particle size is tuned, and particles are formed with and without hemoglobin. The encapsulation efficiency and ferrous state of hemoglobin are analyzed, resulting in 60% encapsulation efficiency and a maximum of 20% ferric hemoglobin, yielding 100 μg mL−1 active hemoglobin in certain silk fibroin‐HBOCs formulations. The system does not elicit a strong inflammation response in vitro, demonstrating the potential for this particle system to serve as an injectable HBOC.